Multiple Intelligences In The Development Of Lexical Competence (2016)
The aim of this research project is to determine in what extent the implementation of the musical intelligence influences the lexical competence of students of 9th grade from John Dewey School. This project was carried out in a private institution in Calarcá Quindio with a population sample of 14 students between 14 and 15 years old. The analysis of the results showed a positive impact in the motivation of students in learning English, this motivation is due to the musical component and the topics chosen by the research teacher that were based on their age and their interests, this combination make the classes understandable and enjoyable.